A review on the properties, performance and emission aspects of the third generation biodiesels. (February 2018) - Sakthivel, R.; Ramesh, K.; Purnachandran, R.; Mohamed Shameer, P.
Abstract: In the effect of robust industrialization and rapid augmentation of a number of fleets, there has been a huge rise in the fossil fuel consumption. Tremendous increase in global warming threatens the ecological balance of the earth. Based on the recent sorts of hardship about the fuel, researchers are profoundly pondered over the field of renewability, environmentally friendly and economically doable. In recent decades biodiesel fuel becomes the center of attraction among researchers since it is renewable, bio degradable, non-noxious, eco-friendly and sustainable. This review paper highlights and reviews the properties of prosperous variety of the biodiesel fuels derived from non-edible feedstocks which are termed as third generation biodiesel and its effects on the performance and emissions of the diesel engines. It was observed that the physicochemical properties of the biodiesel differ based on the types of feedstocks and also have a considerable effect on the potential performance of engine and dynamic characteristics of emission level. Also, the usage of biodiesel commonly leads to a reduction in noxious pollutants like carbon monoxide, unburnt hydrocarbon and particulate matter with an obvious increase in fuel consumption and NOx emission. This review provides a prospective strategy for the researchers for enhancing the engine performance and emission characteristics by using the third generation biofuels and its blends with the productive marvelous outcomes.